Insertion of CO2 Mediated by a (Xantphos)NiI–Alkyl Species. (15th August 2019) - Diccianni, Justin B.; Hu, Chunhua T.; Diao, Tianning
Abstract: The incorporation of CO2 into organometallic and organic molecules represents a sustainable way to prepare carboxylates. The mechanism of reductive carboxylation of alkyl halides has been proposed to proceed through the reduction of Ni II to Ni I by either Zn or Mn, followed by CO2 insertion into Ni I ‐alkyl species. No experimental evidence has been previously established to support the two proposed steps. Demonstrated herein is that the direct reduction of ( t Bu‐Xantphos)Ni II Br2 by Zn affords Ni I species. ( t Bu‐Xantphos)Ni I ‐Me and ( t Bu‐Xantphos)Ni I ‐Et complexes undergo fast insertion of CO2 at 22 °C. The substantially faster rate, relative to that of Ni II complexes, serves as the long‐sought‐after experimental support for the proposed mechanisms of Ni‐catalyzed carboxylation reactions. Abstract : Unterstützung sammeln : Der Einbau von CO2 in metallorganische und organische Moleküle stellt eine nachhaltige Methode zur Herstellung von Carboxylaten dar. Es wird gezeigt, dass die direkte Reduktion von ( t Bu‐Xantphos)Ni II Br2 durch Zn einen Zugang zu Ni I ‐Spezies ermöglicht. ( t Bu‐Xantphos)Ni I ‐Me‐ und ( t Bu‐Xantphos)Ni I ‐Et‐Komplexe durchlaufen eine schnelle Insertion von CO2 bei 22 °C und stützen damit experimentell die vorgeschlagenen Mechanismen der Ni‐katalysierten Carboxylierungsreaktionen.